Implementation of Fuzzy Logic in the Oven Temperature Control System and The Length of Time in The Baking Process for Nastar Products - Agus Miftah Nur Rizqi; Nanda Octavia; Ester Angeline; Fiqri Nurfadillah; Muhammad Danang Mukti Darmawan; Viska Putri Prisillia; Rini Yuni Sara Situmorang; Nisrina Mutiara Anandha; Nadia Nur Azizah; Mutiara Vania Hesti; Hanan Luthfan Hafizh; Gita Khaerunnisa; Ghaisya Raihana; Dinda Ayu Prameswari; Dennaya Mustika; Aidil Hidayat; Mrr. Lukie Trianawati (Journal of Applied Science, Technology & Humanities | JASTH, 2024)
This research focuses on the effect of oven temperature and roasting time on cookie products, especially Nastar, produced for specific events. The right temperature and roasting time will affect the quality and characteristics of Nastar that consumers will accept. A tool called fuzzy logic selects Nastar's optimal temperature and baking time. Fuzzy logic is a mathematical method that uses computer intelligence to determine Nastar's temperature and baking time. The data used in this research was obtained from previous research and then analyzed using the fuzzy logic method. The temperature variables used in this research are Low temperature (80, 100, 1200C), Medium temperature (110, 130, 1500C), and High temperature ( 140, 160, 1800C) and the roasting time variables are Short time (0, 0, 5, 10 minutes) and Longtime (10, 15, 20, 20 minutes). This research shows that the optimal temperature for Nastar is 1150C with a baking time of 18 minutes. This result is based on calculations carried out using the Matlab application.